2018
DOI: 10.21566/tarbitderg.501484
|View full text |Cite
|
Sign up to set email alerts
|

Bazı Buğdaygil Bitki Türlerinin Yem Kalite Değerlerinin Belirlenmesi ve Biplot Analiz Yöntemi ile Özelliklerarası İlişkilerin Değerlendirilmesi

Abstract: Hayvan beslemesinde kullanılacak kaba yemlere ait besin içeriklerinin ve kalite parametrelerinin önceden bilinmesi başarılı bir hayvancılık için büyük öneme sahiptir. Bu çalışma doğal olarak yetişen bazı buğdaygil yem bitkisi türlerinin yem kalitesini belirlemek amacıyla yürütülmüştür. Dicle Üniversitesi kampüs alanında yeralan doğal vejetasyondan 2017 yılında toplanan 13 değişik buğdaygil cinsine ait 15 buğdaygil yem bitkisi türü, araştırmanın materyalini oluşturmuştur. Bitki türlerine ait doğadan toplanan to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
(1 reference statement)
0
1
3
Order By: Relevance
“…During the maturation period, the changes in plant cell wall components lead to an increase in ADF content (Kaplan et al, 2017). On the other hand, the differences between the previous and current study findings were due to genotypical, ecological, cultural, and analytical factors (Başbağ et al, 2018).…”
Section: Acid Detergent Insoluble Fiber (%) and Neutral Detergent Insoluble Fiber (%)contrasting
confidence: 89%
See 3 more Smart Citations
“…During the maturation period, the changes in plant cell wall components lead to an increase in ADF content (Kaplan et al, 2017). On the other hand, the differences between the previous and current study findings were due to genotypical, ecological, cultural, and analytical factors (Başbağ et al, 2018).…”
Section: Acid Detergent Insoluble Fiber (%) and Neutral Detergent Insoluble Fiber (%)contrasting
confidence: 89%
“…The previous studies on ADP reported that it varied between 0.08 and 0.63% in certain poaceous species (Başbağ et al, 2018). The present study findings were higher than those reported in previous studies.…”
Section: Acidic Detergent Insoluble Protein (%) and Digestible Dry Matter (%)contrasting
confidence: 84%
See 2 more Smart Citations